The right hemisphere contribution to semantic categorization: A TMS study. (March 2015) - Passeri, Alessandra; Capotosto, Paolo; Di Matteo, Rosalia
Abstract: A large amount of evidence suggests an involvement of the right hemisphere in lexical-semantic processing, but its specific contribution compared to the left hemisphere is not entirely clear. The present study investigated the contribution of both hemispheres to the semantic categorization process of words referring to typical and atypical exemplars. Transcranial Magnetic Stimulation (TMS) was used to interfere with the online activity of Wernicke's area and its right homologue during a verbal category membership task. The TMS delayed the responses to typical member nouns compared to the control condition, over both areas of interest. On the contrary, a delay in the responses to atypical member nouns was observed only when the right Wernicke's area was stimulated. Overall, these results indicate that while both hemispheres are involved in the categorization of typical exemplars, the right hemisphere specifically contributes to semantic categorization of atypical ones.